Philosophically speaking, how many species concepts are there? - Wilkins, John S. (Zootaxa, 2011)
It’s an old question in biology: what is a species? Many different answers have been given over the years, and there are indefinitely many “definitions” in the literature. Adding to R. L. Mayden’s list of 22 definitions (Mayden, 1997) , I counted 26 in play since the Modern Synthesis (2009a), and a new one, which I call the “polyphasic” concept (basically a consilience of many lines of morphological, ecological, genetic, and physiological evidence), has been implicitly extended from bacterial and other microbial contexts to macrobial species, although the terminology has not yet been transplanted (Colwell, 1970; Vandamme et al., 1996). However, on another count there are seven “basic” species concepts: agamospecies (asexuals), biospecies (reproductively isolated sexual species), ecospecies (ecological niche occupiers), evolutionary species (evolving lineages), genetic species (common gene pool), morphospecies (species defined by their form, or phenotypes), and taxonomic species (whatever a taxonomist calls a species).